HUBUNGAN ANTARA AKTIVITAS FISIK DAN POLA TIDUR DENGAN KEJADIAN HIPERTENSI - Nasution, Andreanda; Nauli, Humaira Anggie; Anggraini, Sevrima; Alfaeni, Siti Walidaturrahmah; Dahliawati, Anis (Poltekkes Kemenkes Bandung, 2024)
Hypertension is a non-communicable disease which is currently the main cause of health problems. The research aimed to determine the relationship between physical activity and sleep patterns and incidence of hypertension in the Pancasan Community Health Center Area, Bogor City. This research was quantitative research with observational methods using a cross-sectional design. This research used the Chi square analysis test. This research was conducted in the working area of the Pancasan Health Center in Bogor City for 4 months from April to July 2023. Sample inclusion criteria are domiciled in the Pancasan Community Health Center working area, hypertensive and non-hypertensive patients aged 21-60 years, hypertensive patients with systolic blood pressure of 140-179 mmHg and diastolic blood pressure of 90-109 mmHg, and who are willing to be respondents by signing the information consent when collecting data for both patients with hypertension and without hypertension. Sampling in this study was done using the simple random sampling technique. The sample size in this study used the Lemeshow Formula so 57 samples were obtained. The results showed an association between the level of physical activity and the incidence of hypertension (P=0.028) and a relationship between hypertension and poor sleep patterns (P=0.003). In conclusion, low physical activity increases the risk of hypertension, while moderate activity has four times the chance of not developing hypertension. Sleep patterns are significantly related to the incidence of hypertension where respondents who have good sleep patterns have a lower chance of developing hypertension compared to respondents who have poor sleep patterns.